Pengembangan Media Evaluasi Labirin Berbasis Kontekstual Materi FPB dan KPK Mata Pelajaran Matematika Kelas V SD - Nurfahliza Ramadhani; Mimin Ninawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to develop a contextual-based labyrinth evaluation media for FPB and KPK materials in mathematics. This study uses the Research and Development (R&D) method, where the author uses a 4D model as a support for this research which has four stages, namely: 1. Definition, 2. Design, 3. Development, 4 .Dessiminate. The development of this labyrinth media got results in the form of validation from two experts, both media and material experts. As well as getting results regarding student responses related to the maze as a learning evaluation medium. The results of the experts, both media and material experts, have the same score, namely 93%, which is categorized as very valid. As for the results of the students' responses, they got a score of 95% and got a very good category. It can be concluded that the contextual-based labyrinth evaluation media for FPB and KPK grade V SDS Juara West Jakarta is very valid for use in the mathematics learning process, especially in the evaluation process. Keywords: Labirin, contextual, mathematic